PB3. Pharyngeal Electrical Stimulation in neurointensive care patients suffering from severe post-stroke dysphagia – Post stimulation increase of salivary substance P level may indicate treatment success. Issue 8 (August 2018) - Muhle, P.; Suntrup-Krueger, S.; Bittner, S.; Ruck, T.; Claus, I.; Marian, T.; Schröder, J.B.; Minnerup, J.; Warnecke, T.; Meuth, S.G.; Dziewas, R.
Abstract : Introduction: Dysphagia is one of the most important and prognostically relevant complications of acute stroke. Pharyngeal Electrical Stimulation (PES) is a treatment device that enhances cortical reorganization for the restoration of swallowing function after cerebral injury. Furthermore, it was shown that PES leads to a temporary increase of Substance P (SP) level in saliva but not serum in healthy adults. The neuropeptide SP likely acts as a neurotransmitter in the pharyngeal mucosa and enhances the swallow and cough reflex. Post-stroke dysphagia may be related to reduced SP-levels. Here, we investigated the association of PES treatment in neurointensive care patients suffering from severe post-stroke dysphagia and salivary SP level, as well as a possible link between SP level and decannulation success after PES. Material and methods: In this prospective single-center study, 23 tracheotomized stroke patients from our neurological intensive care unit were included. Due to severe and persisting dysphagia and according to the protocol for standardized endoscopic evaluation of tracheotomy decannulation in critically ill neurologic patients, participants could not be decannulated. Comorbidities that are known to likely cause dysphagia were not an exclusion criterion in contrast to other studies investigating on PES. 10 min of PES were applied on three consecutive days (= one treatment cycle). Three patients received multiple stimulation cycles. Saliva samples were collected prior to and directly after each treatment. To determine SP concentration, Enzyme-linked immunosorbent assay (ELISA) was performed. Results: After the first treatment cycle 60% ( n  = 14) of all participants, respectively 73% ( n  = 7) of patients without comorbidities that likely cause dysphagia were decannulated. There was a close relation between increase of SP directly after the treatment and stimulation success (= decannulation). In 89% ( n  = 9) of patients without clinical improvement of dysphagia, SP levels remained stable or even decreased; 79% ( n  = 11) of successfully treated patients showed a post-stimulation increase of SP. Applying logistic regression analysis, increased SP level showed to be independently predictive of improved swallowing function after PES (p < 0.05). Of the three patients who received multiple treatment cycles, an increase of mean SP level was found when progressing from the 1st to the 2nd treatment cycle. This trend was continued when a 3rd PES cycle was applied in one patient. Two of the three multiply treated patients were decannulated after repetitive PES treatment cycles according to the before mentioned endoscopy-based protocol. Conclusion: The increase of salivary SP level following PES may indicate treatment success and SP therefore possibly acts as a biomarker of an improved swallowing function following PES.